Hippocampal Homer1 levels influence motivational behavior in an operant conditioning task. - Klaus V Wagner (Public Library of Science (PLoS), 2014)
Loss of motivation and learning impairments are commonly accepted core symptoms of psychiatric disorders such as depression and schizophrenia. Reward-motivated learning is dependent on the hippocampal formation but the molecular mechanisms that lead to functional incentive motivation in this brain region are still largely unknown. Recent evidence implicates neurotransmission via metabotropic glutamate receptors and Homer1, their interaction partner in the postsynaptic density, in drug addiction and motivational learning. As previous reports mainly focused on the prefrontal cortex and the nucleus accumbens, we now investigated the role of hippocampal Homer1 in operant reward learning in the present study. We therefore tested either Homer1 knockout mice or mice that overexpress Homer1 in the hippocampus in an operant conditioning paradigm. Our results show that deletion of Homer1 leads to a diverging phenotype that either displays an inability to perform the task or outstanding hyperactivity in both learning and motivational sessions. Due to the apparent bimodal distribution of this phenotype, the overall effect of Homer1 deletion in this paradigm is not significantly altered. Overexpression of hippocampal Homer1 did not lead to a significantly altered learning performance in any stage of the testing paradigm, yet may subtly contribute to emerging motivational deficits. Our results indicate an involvement of Homer1-mediated signaling in the hippocampus in motivation-based learning tasks and encourage further investigations regarding the specific molecular underpinnings of the phenotypes observed in this study. We also suggest to cautiously interpret the results of this and other studies regarding the phenotype following Homer1 manipulations in animals, since their behavioral phenotype appears to be highly diverse. Future studies would benefit from larger group sizes that would allow splitting the experimental groups in responders and non-responders.